Controlled drug delivery for surface protection of prostheses - Carmo, Catarina Paulino Cidade do (2022)
This work aimed to study the application of a multilayer polymeric coating on stainless-steel (SS) sur- faces to provide local and controlled drug delivery to prevent the formation of biofilms. The bacteria colonies formed onto non-recognized surfaces placed inside the body could cause serious infections leading to the im- plant’s removal. Therefore, implant’s surface functionalization is a key point to overcome this problem. Using electrospinning and blow-spinning techniques, the SS substrates were coated layer-by-layer with membranes made of cellulose acetate (CA) and polycaprolactone (PCL) fibres containing ibuprofen (Ibu). The fibres retain the mechanical properties of the polymers while also allow for controlled Ibu release in specific locations. As a result, Ibu efficacy improves and the ability of implant rejection decreases. Optical microscopy, scanning electron microscopy, and Raman spectroscopy were used to characterize the fibres. Following the films production, drug release, swelling, and degradation tests were carried out to simu- late in vivo performance of the membranes. Mechanical properties were also evaluated through stress and peeling-off adhesion tests. A layer of chitosan (CHI) was electrosprayed between the substrate and the coating for the peeling-off tests, to evaluate the effect of CHI on adhesion. Ibu was successfully incorporated into the fibres, but the concentrations and control of its release require further investigation. The electrosprayed CHI layer improved the adhesion of the coating to the surfaces. In conclusion, this research has demonstrated that the films obtained have promising properties for use in the context of implant-related infection treatment.